Spring on Loop

Note- Please type the option number in the answer box.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Steven Chase
Sep 19, 2017

Initial spring potential energy:

U 0 = 1 2 k ( 2 R ) 2 = 2 k R 2 U_0 = \frac{1}{2} k (2R)^2 = 2k R^2

Spring potential energy as a function of θ \theta , where θ \theta is the angle between the displacement vector (from origin) and the vertical.

x = R s i n θ y = R c o s θ Δ x = x = R s i n θ Δ y = y + R = R c o s θ + R U = 1 2 k ( ( Δ x ) 2 + ( Δ y ) 2 ) = 1 2 k ( 2 R 2 ) ( 1 + c o s θ ) = k R 2 ( 1 + c o s θ ) x = R \, sin\theta \\ y = R \, cos\theta \\ \Delta x = x = R \, sin\theta \\ \Delta y = y + R = R \, cos\theta + R \\ U = \frac{1}{2} k ((\Delta x)^2 + (\Delta y)^2) = \frac{1}{2} k (2R^2)(1 + cos\theta) = k R^2(1 + cos\theta)

Change in spring potential energy:

Δ U = U 0 U = 2 k R 2 k R 2 ( 1 + c o s θ ) = k R 2 ( 1 c o s θ ) \Delta U = U_0 - U = 2k R^2 - k R^2(1 + cos\theta) = k R^2(1 - cos\theta)

Equate Δ U \Delta U to the kinetic energy:

Δ U = 1 2 m v 2 m v 2 = 2 k R 2 ( 1 c o s θ ) \Delta U = \frac{1}{2} mv^2 \implies mv^2 = 2k R^2(1 - cos\theta)

Calculate centripetal force:

F c = m v 2 R = 2 k R ( 1 c o s θ ) F_c = \frac{mv^2}{R} = 2k R(1 - cos\theta)

Spring force in the radial direction (by inspection):

F s r = 2 k R 1 + c o s θ c o s ( θ 2 ) F_{sr} = \sqrt{2} kR \sqrt{1 + cos\theta} \,\, cos(\frac{\theta}{2})

There is no reaction force when the centripetal force is equal to the spring force in the radial direction:

2 k R ( 1 c o s θ ) = 2 k R 1 + c o s θ c o s ( θ 2 ) 2 ( 1 c o s θ ) = 1 + c o s θ c o s ( θ 2 ) = 1 + c o s θ 1 + c o s θ 2 2 ( 1 c o s θ ) = 1 + c o s θ c o s θ = 1 3 2k R(1 - cos\theta) = \sqrt{2} kR \sqrt{1 + cos\theta} \,\, cos(\frac{\theta}{2}) \\ \sqrt{2}(1 - cos\theta) = \sqrt{1 + cos\theta} \,\, cos(\frac{\theta}{2}) = \sqrt{1 + cos\theta} \frac{\sqrt{1 + cos\theta}}{\sqrt{2}} \\ 2(1-cos\theta) = 1 + cos\theta \\ cos\theta = \frac{1}{3}

Final stretch calculation:

( Δ x ) 2 + ( Δ y ) 2 = ( 2 R 2 ) ( 1 + c o s θ ) = ( 2 R 2 ) ( 1 + 1 3 ) = R 8 3 \sqrt{(\Delta x)^2 + (\Delta y)^2} = \sqrt{(2R^2)(1 + cos\theta)} = \sqrt{(2R^2)(1 + \frac{1}{3})} = \boxed{R \sqrt{\frac{8}{3}}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...